2023
DOI: 10.4317/medoral.25613
|View full text |Cite
|
Sign up to set email alerts
|

Oral paracoccidioidomycosis: a retrospective study of 95 cases from a single center and literature review

Abstract: Background The ecoepidemiological panorama of paracoccidioidomycosis (PCM) is dynamic and still ongoing in Brazil. In particular, data about the oral lesions of PCM are barely explored. The aim of this study was to report the clinicopathological features of individuals diagnosed with oral PCM lesions at an oral and maxillofacial pathology service in Rio de Janeiro, Brazil, in the light of a literature review. Material and Methods A retrospective study was conducted on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
0
1
Order By: Relevance
“…The oral cavity/oropharynx are commonly affected in PCM. 61 , 62 The PCM OOPML frequency in our study was proportionally higher than that of other studies when considering the duration of the studies, 51 , 62 including that observed in a study carried out in a region with high PCM prevalence. 63 This higher prevalence is likely owing to the fact that our service is a reference center for infectious diseases and conducts the systematic otorhinolaryngological examination of patients referred by other services.…”
Section: Discussioncontrasting
confidence: 66%
“…The oral cavity/oropharynx are commonly affected in PCM. 61 , 62 The PCM OOPML frequency in our study was proportionally higher than that of other studies when considering the duration of the studies, 51 , 62 including that observed in a study carried out in a region with high PCM prevalence. 63 This higher prevalence is likely owing to the fact that our service is a reference center for infectious diseases and conducts the systematic otorhinolaryngological examination of patients referred by other services.…”
Section: Discussioncontrasting
confidence: 66%
“…The epidemiology of oral PCM demonstrates a higher incidence in middle-aged or older male adults [13,14].…”
Section: Paracoccidioidomycosis (Pcm) Is a Systemic Mycosis Typical O...mentioning
confidence: 99%
“…No entanto, essa infecção não se limita apenas aos pulmões, pois o fungo pode se disseminar para outros órgãos do corpo, resultando em lesões secundárias e complicações adicionais, inclusive manifestações orais que devem ser notadas pelo cirurgião-dentista numa consulta de rotina. 2 A Paracoccidioidomicose é mais comum em trabalhadores rurais de meia-idade, sendo este o perfil mais comum de pessoas infectadas uma vez que estão frequentemente expostos ao solo onde o fungo reside. A natureza insidiosa dessa infecção torna essencial a conscientização sobre seus sintomas e riscos, bem como a busca por tratamento adequado o mais cedo possível.…”
Section: Introductionunclassified

Paracoccidioidomicose oral

Soares Zappalá,
César Guimarães,
Oliveira Teles
et al. 2024
R.CROMG